KAJIAN KEBERLANJUTAN PROGRAM YAYASAN PEMBANGUNAN BERKELANJUTAN SULAWESI UTARA (YPBSU) PASCA PENUTUPAN TAMBANG PT. NEWMONT MINAHASA RAYA (PT. NMR) DI KECAMATAN RATATOTOK MINAHASA TENGGARA - Minar Anna Ulina Naibaho; Melissa Lady Gisela Taroreh; Gene Henfried Meyer Kapantow (Sam Ratulangi University, 2021)
This study aims to examine the effectiveness of the programs carried out by the Yayasan Pembangunann Berkelanjutan Sulawesi Utara (YPBSU) after the closure of the gold mine of PT. Newmont Minahasa Raya (PT. NMR). This research was conducted from December 2019 to February 2020 in Ratatotok Sub-District, Southeast Minahasa district by tracing information from the Ratatotok Sub-District community who had received assistance from Yayasan Program Pembangunan Berkelanjutan Sulawesi Utara (YPBSU). The selection of respondents was 13 people using snow balling technique. Analysis of the data used in this study is descriptive analysis. The results showed that only two out of seven economic assistance distributed to the community was effective and five of which were ineffective (unable to continue). This is due to the lack of close supervision from the Yayasan Pembangunan Berkelanjutan Sulawesi Utara (YPBSU) for the assistance that has been distributed to the community